2020
DOI: 10.7554/elife.58374
|View full text |Cite
|
Sign up to set email alerts
|

SOX11 promotes epithelial/mesenchymal hybrid state and alters tropism of invasive breast cancer cells

Abstract: SOX11 is an embryonic mammary epithelial marker that is normally silenced prior to birth. High SOX11 levels in breast tumours are significantly associated with distant metastasis and poor outcome in breast cancer patients. Here, we show that SOX11 confers distinct features to ER-negative DCIS.com breast cancer cells, leading to populations enriched with highly plastic hybrid epithelial/mesenchymal cells, which display invasive features and alterations in metastatic tropism when xenografted into mice. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
(93 reference statements)
1
23
1
Order By: Relevance
“…DOX-induced expression of SOX11 in DCIS.com cells led to increased expression of markers associated with mesenchymal state, increased size of the ALDH + /CD24 + CSC population, and increased frequency of cells expressing both luminal (K8) and basal (K14, SMA) lineage markers. Furthermore, small mammary tumours that formed from cells expressing high levels of SOX11 grew out quickly when DOX chow was replaced with normal chow, suggesting that high levels of SOX11 may keep tumours in a non-proliferative state and that proliferation occurs when SOX11 levels were lowered upon DOX withdrawal ( Oliemuller et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DOX-induced expression of SOX11 in DCIS.com cells led to increased expression of markers associated with mesenchymal state, increased size of the ALDH + /CD24 + CSC population, and increased frequency of cells expressing both luminal (K8) and basal (K14, SMA) lineage markers. Furthermore, small mammary tumours that formed from cells expressing high levels of SOX11 grew out quickly when DOX chow was replaced with normal chow, suggesting that high levels of SOX11 may keep tumours in a non-proliferative state and that proliferation occurs when SOX11 levels were lowered upon DOX withdrawal ( Oliemuller et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Oliemuller et al (2017) showed that constitutive expression of low levels of SOX11 using the CMV promoter led to enhanced invasive growth of ductal carcinoma in situ lesions. A significantly higher level of SOX11 expression was achieved using a doxycycline (DOX)-inducible EF1A promoter (Oliemuller et al, 2020). DOX-induced expression of SOX11 in DCIS.com cells led to increased expression of markers associated with mesenchymal state, increased size of the ALDH + /CD24 + CSC population, and increased frequency of cells expressing both luminal (K8) and basal (K14, SMA) lineage markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism underlying the sometimes severe upregulation of MEX3 protein expression in cancer remains largely elusive. However, in mouse models of breast cancer, MEX3A upregulation was induced by SOX11 [ 53 ], a member of the SOXC transcription factors, consisting of SOX4, SOX11 and SOX12. Next to functions in neuronal development [ 56 ], especially SOX4 and SOX11 were reported to harbor substantial oncogenic potential in various malignancies [ 57 ].…”
Section: A Snapshot View Of Mex3a’s Disease Driving Potential In Cancermentioning
confidence: 99%
“…So far, little is known about the transcriptional control of MEX3 expression. In the human breast cancer cell line MCF10DCIS.com, MEX3A and MEX3B could be identified among the 25 most upregulated targets due to SOX11 overexpression [53]. Sox11 belongs to the SOXC group of transcription factors highly expressed during early embryogenesis and presenting one essential embryonic mammary epithelial marker upregulated in various cancers [54].…”
Section: Roles Of Oncofetal Mex3 Proteins In Driving Tumorigenesismentioning
confidence: 99%